2011
DOI: 10.1111/j.1365-2702.2011.03870.x
|View full text |Cite
|
Sign up to set email alerts
|

Midwives and oral health care during pregnancy: perceptions of pregnant women in south‐western Sydney, Australia

Abstract: Antenatal care providers in Australia should provide more information about oral health. These health professionals should be adequately educated to promote oral health. Health services should also consider offering pregnant women affordable and accessible dental services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
62
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 35 publications
12
62
1
1
Order By: Relevance
“…Unfortunately there are no comparable studies that have explored the oral health awareness of people with CVD or the knowledge among dental professionals. Looking beyond the CVD setting, many patients in maternity, palliative care, immune-compromised and with diabetes are also unaware of the importance of oral health [44–47]. Perhaps of greater concern are the findings from several studies that reported dentists were also often unaware of the impact of poor oral health on systemic conditions [13, 4850].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately there are no comparable studies that have explored the oral health awareness of people with CVD or the knowledge among dental professionals. Looking beyond the CVD setting, many patients in maternity, palliative care, immune-compromised and with diabetes are also unaware of the importance of oral health [44–47]. Perhaps of greater concern are the findings from several studies that reported dentists were also often unaware of the impact of poor oral health on systemic conditions [13, 4850].…”
Section: Discussionmentioning
confidence: 99%
“…Although most pregnant women in Khartoum state receive a comprehensive form of antenatal care from maternity care centres, they do not receive instructions concerning oral health care during pregnancy. A pregnant woman's knowledge and actions concerning her oral health are critical to the oral health of her children and play a vital role in childhood caries prevention (27), and some countries have adopted a strategy of maternal oral health promotion through antenatal care providers (28).…”
Section: Tooth-brushingmentioning
confidence: 99%
“…Also, school‐based oral health prevention programmes be conducted within schools because school‐aged adolescents are in special need of preventive programme to ensure positive long‐term oral and dental health. Possibility of visit at home, providing free in‐home services, understanding the pregnant women's conditions, supervision over the implementation of oral health programmes in pregnant women and attention of the concerned authorities and healthcare providers to the educational programmes are measures that government can adopt to improve oral health in pregnant women …”
Section: Discussionmentioning
confidence: 99%